Markups of Exporters and Importers: Evidence from Hungary - Cecilia Hornok; Balázs Muraközy (Kiel Centre for Globalization (KCG), 2018)
This paper studies the relationship between firm-level markups and trade status using balance sheet information linked to detailed trade data from Hungary between 1995-2003. We find that importing is strongly positively correlated with markups both across and within firms. We argue that this correlation can reflect three channels: self-selection, higher physical productivity resulting from access to a larger variety of inputs and quality upgrading based on high-quality imported intermediate inputs. We present evidence for the relevance of the latter channel by showing that the markup premium is higher when inputs arrive from developed countries and that importing is correlated with higher quality exports. We find limited evidence for exporter premium when controlling for importing. We argue that the small exporter premium results from the stronger competition in export markets relative to domestic ones. Our results strengthen arguments for policy focusing on promoting imports as a source of increased firm-level competitiveness.
Keywords: D22; D24; F14; L11; L60; 330; markup premia; detailed trade data; quality; self-selection